Pengaruh Bokashi Limbah Bunga Jantan Kelapa Sawit Terhadap Pertumbuhan dan Hasil Tanaman Edamame - Hairullah Hairullah; Tuti Heiriyani; Noor Khamidah (Agroekotek View, 2021)
Oil palm plantations in South Kalimantan are large enough to produce a lot of waste in the form of male flowers. Oil palm male flowers have not been used optimally, but have the potential to be used as organic fertilizer or bokashi because they contain nutrients which are then able to support growth in plants and fertilize the soil (Hamidiyanto, 2012). Edamame soybean production in South Kalimantan is still minimal, so it needs to be increased, one of which is the use of bokashi fertilizer. The utilization of oil palm male flower waste into bokashi is expected to increase the amount of growth and yield of edamame plants. The research was carried out from February-May 2020 in the land around the greenhouse of the Agroecotechnology Department, Faculty of Agriculture, Lambung Mangkurat University, and the Laboratory for Commodity and Environmental Testing of the Banjarbaru Industrial Research and Standardization Center (BARISTAND). The design in this study was a completely randomized design (CRD) with one factor, namely the provision of bokashi waste from male oil palm flowers with different doses, namely K1 = 160 grams of bokashi, K2 = 180 grams of bokashi, and K3 = 200 grams of bokashi. The results showed that the application of bokashi from oil palm male flower waste on K2 treatment of 180 grams of bokashi and K3 of 200 grams of bokashi had a significant effect on plant height and number of leaves and number of pods in edamame plants, but did not significantly affect the dry weight of 100 seeds. The best dose of bokashi for yield and growth of edamame plants is the treatment of K2 = 180 grams.